PENERAPAN SISTEM PEMBELAJARAN SHIFT YANG IDEAL DI KABUPATEN SUMBA TIMUR - Riwa Rambu Hada Enda (Universitas Muhammadiyah Surakarta, 2022)
Learning from homeapplied in East Sumba is a distance learning Shift. This Shift learning system is done by dividing class levels. This research is R and D research, that focus on application of implementation, the application of the results of previous studies which is the development of the ideal distance learning model in East Sumba by using Addie model. The implementation of the Shift Research Results Guidelines was carried out in Kambera Public Middle School with quesioners, interview and FGD as data collection technique. The results of this study indicate that in: 1) preparation stage, the principal, parents and regional government has conducted a distance learning shift in accordance with the guidelines, while students and teachers have not implemented the preparation according to the guidelines because many students do not prepare health protocol devices while many teachers do not prepare props and video learning; 2) Implementation stage, students, teachers, principals and regional governments have conducted a distance learning Shift in accordance with the guidelines, while parents are not in accordance with the guidelines because parents do not accompany students in carrying out Shift learning at school; 3) Evaluation stage, students, teacher, principals, and local government has conducted a distance learning Shift in accordance with the guidelines, while parents are not in accordance with the guidelines because parents do not accompany students in taking the results of the evaluation of children in school and do not provide feedback to the assessment results.